2007
DOI: 10.3132/dvdr.2007.030
|View full text |Cite
|
Sign up to set email alerts
|

The ApoAI-CIII-AIV gene cluster and its relation to lipid levels in type 2 diabetes mellitus and coronary heart disease: determination of a novel susceptible haplotype

Abstract: The present study investigated genetic variation in the 3' flanking region of ApoA-I (PstI), the 3' untranslated region of ApoC-III (SstI) and intron 2 of ApoA-IV (XbaI) in 435 type 2 diabetes mellitus patients, divided according to the presence or absence of coronary heart disease (CHD). Uncommon allele frequencies (P2, S2, X2) were 17.5%, 32.5%, 16.2% and 29.5%, 17.9%, 13.8% in patients with and without CHD, respectively. Linkage disequilibrium (D' = 0.31-0.73, p<0.01) was observed in all diallelic pairs exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Other genes having roles in metabolism have been identified. APOA1 is the major component of high density lipoprotein in plasma and SNPs in APOA1 gene have been associated with the risk of cardiovascular diseases [141] and with T2D [142]. Zhang et al observed that the microbiota of APOA1 -deficient mice has a different community structure in comparison with that of wild-type mice [143].…”
Section: Gut Microbiota-host Genes Crosstalk and Role Of The Dietmentioning
confidence: 99%
“…Other genes having roles in metabolism have been identified. APOA1 is the major component of high density lipoprotein in plasma and SNPs in APOA1 gene have been associated with the risk of cardiovascular diseases [141] and with T2D [142]. Zhang et al observed that the microbiota of APOA1 -deficient mice has a different community structure in comparison with that of wild-type mice [143].…”
Section: Gut Microbiota-host Genes Crosstalk and Role Of The Dietmentioning
confidence: 99%
“…In the Indian population, rs12721026 was associated with increased risk for type II diabetes [48]. Our results showed an association of the rs1729408 C-allele and higher HbAc1 levels.…”
Section: Discussionmentioning
confidence: 44%
“…Subjects taking estrogens or having other affiliated diseases like renal and hepatic insufficiency were excluded. The details of study design were described elsewhere [6,7]. After DNA extraction with phenol chloroform, the genotypes of ApoE and ApoA-I/ 3′ flanking region were determined by PCR RFLP using the restriction enzymes HhaI and PstI respectively.…”
Section: Methodsmentioning
confidence: 99%